Prevalence and Fall Risk of Sarcopenia Based on the 2023 Korean Working Group on Sarcopenia Criteria - Minjung Kim; Seongmin Choi; Dong Hwan Yun; Yunsoo Soh; Chang Won Won (Medicina)
Background and Objectives: Sarcopenia is a major risk factor for falls in older adults. The 2023 Korean Working Group on Sarcopenia (KWGS) introduced revised definitions, including functional sarcopenia, which considers low strength and performance despite normal muscle mass. This study investigated the prevalence of sarcopenia, severe sarcopenia, and functional sarcopenia using the KWGS criteria and their association with fall risk by sex and fall frequency. Materials and Methods: A cross-sectional analysis was conducted using data from 2061 community-dwelling Korean adults aged 70–84 years who participated in the Korean Frailty and Aging cohort study. Sarcopenia was classified based on muscle mass, grip strength, and four physical performance tests. Fall experiences in the past year were categorized as ≥1, ≥2, and ≥4 falls. Logistic regression analyses were performed separately according to sex to evaluate the association between sarcopenia definition and fall risk. Results: The prevalence of sarcopenia and severe sarcopenia was 32.9% and 10.1% in men and 21.5% and 5.0% in women, respectively. Functional sarcopenia was more prevalent in women (10.5%) than in men (5.1%). In men, sarcopenia (defined using gait speed) was associated with fall risk across all thresholds (odds ratio [OR] = 2.28 for ≥1 fall; OR = 5.64 for ≥4 falls). In women, sarcopenia (defined using gait speed) was associated with ≥1 fall (OR = 1.72), while functional sarcopenia (defined using gait speed and timed up-and-go test) was associated with frequent falls (OR = 3.79–3.87). Conclusions: The 2023 KWGS guidelines revealed sex-specific differences in the prevalence of sarcopenia and highlighted gait speed as a key predictor of fall risk in men, whereas functional sarcopenia was more prevalent in women. Limitations include the cross-sectional design and use of self-reported fall data, which may be subject to recall bias.